2015
DOI: 10.3168/jds.2014-8877
|View full text |Cite
|
Sign up to set email alerts
|

The effects of firocoxib on cautery disbudding pain and stress responses in preweaned dairy calves

Abstract: Perioperative analgesic effects of oral firocoxib following cautery disbudding were investigated in preweaned calves. Twenty Holstein calves approximately 4 to 6wk old received a single oral dose of firocoxib, a nonsteroidal antiinflammatory, at 0.5mg/kg (n=10) or placebo (n=10) in a randomized controlled clinical trial. Responses, including ocular temperature determined by infrared thermography, pressure algometry measuring mechanical nociception threshold, and heart rate, were evaluated at 2, 4, 7, 8, and 24… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
68
1
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(80 citation statements)
references
References 38 publications
(74 reference statements)
5
68
1
4
Order By: Relevance
“…Stewart et al (2009) reported a decreased ocular temperature associated with the loss of local anesthesia following dehorning. Moreover, administration of meloxicam attenuated the decreased ocular temperature observed in placebo-treated calves after dehorning (Stewart et al, 2009); however, other investigations have not observed this same response Allen et al, 2013;Stock et al, 2015). Differences in handling, study animals, and data collection technique may account for the different results among studies.…”
Section: Ocular Temperaturementioning
confidence: 44%
See 2 more Smart Citations
“…Stewart et al (2009) reported a decreased ocular temperature associated with the loss of local anesthesia following dehorning. Moreover, administration of meloxicam attenuated the decreased ocular temperature observed in placebo-treated calves after dehorning (Stewart et al, 2009); however, other investigations have not observed this same response Allen et al, 2013;Stock et al, 2015). Differences in handling, study animals, and data collection technique may account for the different results among studies.…”
Section: Ocular Temperaturementioning
confidence: 44%
“…No other differences were observed between treatment groups (P > 0.1). Changes in ADG are equivocal, with previous studies reporting no changes or increases compared with placebo-treated controls (Baldridge et al, 2011;Glynn et al, 2013;Coetzee et al, 2012 ;Stock et al, 2015). Greater increases were observed in older study populations undergoing amputation dehorning, suggesting the potential that dehorning has a larger impact on weight gain in older calves after an invasive procedure (Baldridge et al, 2011;Glynn et al, 2013;Coetzee et al, 2012 ).…”
Section: Average Daily Gainmentioning
confidence: 48%
See 1 more Smart Citation
“…The dose was rounded to the nearest 0.01 g of paste. This dose was selected based on pharmacokinetic studies of other NSAIDs in goats and other ruminants (Ingvast‐Larsson et al, ; Karademir, Akin, et al, ; Karademir, Erdogan, et al, ; Stock et al, , ).…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, dogs had a bioavailability of only 38% when administered at 5 mg/kg in fasted animals (FDA, 2004). Limited data are available on the use of oral and intravenous firocoxib in preruminating calves (Stock, Gehring, Barth, Wulf, & Coetzee, 2014;Stock et al, 2015), and a single publication details the use of intravenous firocoxib in adult camels (Wasfi et al, 2015).…”
mentioning
confidence: 99%